Cellular energy allocation of Glyphodes pyloalis (Lep.: Pyralidae): changes related to exposure to TiO2 nanoparticles - N. Memarizadeh; M. Ghadamyari; M. Adeli; Kh. Talebi-Jahromi (نامه انجمن حشره‌شناسی ایران, 2014)
In order to study the pollution potential of TiO2 nanoparticles (TiO2-NPs) on ecological health, this research was carried out on the cellular energy allocation (CEA) of Glyphodes pyloalis Walker exposed to TiO2-NPs. The newly ecdysed fifth instar larvae of G. pyloalis were treated with LC10, LC20, LC30, LC40 and LC50 concentrations of TiO2-NPs and the amount of energy available (Ea), energy consumption (Ec) and cellular energy allocation were compared. The resulting calculated energy reserves (lipid, carbohydrate, glycogen and protein) showed that increasing the time of exposure, the total lipid and carbohydrate amounts significantly decreased, when the LC30, LC40 and LC50 concentrations were applied. The amounts of glycogen in the larvae treated with LC10, LC20 and LC30 concentrations of TiO2-NPs were increased, whereas the LC40 and LC50 concentrations led to decrease in the amount of glycogen. The significant reduction in the amount of total protein compared to the control and over all three days of treatment was observed for LC50 concentration of TiO2-NPs; however, the LC10 concentration lead to a significant increase of the total protein after three days. Ea decreased in a dose-response related manner and over all time points, but it significantly increased in treated larvae by LC10 and LC20 concentrations after two days. Ec increased as concentrations grew to LC30 and then started to decrease. The results showed that CEA was not affected by LC10 concentration, but significantly decreased when the concentration increased and at all time points probably as a cost to deal with TiO2-NPs detoxification. Therefore, it will be possible to use the CEA as an appropriate early biomarker for the impacts of TiO2-NPs.